High-sensitivity capsule-shaped sensor based on 2D photonic crystals - Maache M.; Fazea Y.; Hassan I.B.; Alkahtani A.A.; Din I.U. (MDPI AG, 2023)
This paper presents a new capsule-shaped sensor to detect the glucose concentration in the human body. The model under study was formulated by relying on the index change in the refractive index (RI) because of the change in the sample that infiltrated the cavity. The index of refraction change is accompanied by modifying the resonant wavelength. The recommended model has considered the simple shape and ease of manufacture, along with other characteristics such as sensitivity and a low detection limit. The results report a high sensitivity of S = 546.72 nm/RI unit (RIU), a high quality factor of Q = 2066.24, a low detection limit of DL = 1.44 10-4 RIU, and a high value of transmission of 97%, which are considered to be sufficient and efficient in detecting measured material. This proposed model provides many opportunities and is promising for the manufacture of different types of sensing detection devices. 2020 by the authors.